2009
DOI: 10.4314/afrrev.v3i3.47509
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical Stability Studies of Neem (<i>Azadirachta indica</i>) Seed Oil Cream

Abstract: Neem oil cream is a semi solid formulation that is being developed for its

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…But, that study has revealed that hypericin content varies from a mere 5% to just 50% of the label claim (0.3%). Similarly, content of Azadirachtin A is found to vary significantly (617.3 to 1149.65 ppm) in different batches of neem oil formulations (Aremu and Femi‐Oyewo, ). These studies suggest that similar products from different manufacturers may have widely variable content of marker(s).…”
Section: Challenges In Stability Testing Of Herbal Drugs/productsmentioning
confidence: 94%
“…But, that study has revealed that hypericin content varies from a mere 5% to just 50% of the label claim (0.3%). Similarly, content of Azadirachtin A is found to vary significantly (617.3 to 1149.65 ppm) in different batches of neem oil formulations (Aremu and Femi‐Oyewo, ). These studies suggest that similar products from different manufacturers may have widely variable content of marker(s).…”
Section: Challenges In Stability Testing Of Herbal Drugs/productsmentioning
confidence: 94%
“…Droplet size is an important factor for stability of oil emulsion, droplet size in nano range results in good stability of an emulsion, normally surfactants stabilize oil-in-water emulsion reported that surfactants with lower Hydrophile-Lipophile balance HLB value (3)(4)(5)(6) favors the formation of water-in-oil emulsion and surfactants with higher HLB value (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) favor the formation of oil-in-water emulsion. Tween20 was opted for making oil-in-water emulsion because of its high HLB value of 16.7, which favors formation of oil-in-water type of emulsion.…”
Section: Effect Of Sonication Time and Tween 20 Concentration On Stabmentioning
confidence: 99%
“…Nanoemulsions are prepared by low-energy methods such as phase inversion temperature (PIT) emulsification, by phase inversion composition or by high shear forces using high-pressure homogenizers or ultrasonic generators. 5,6 E. Mixed emulsions: these are systems consisting of two different disperse droplets that do not mix in a continuous medium.…”
Section: Introductionmentioning
confidence: 99%
“…They are thermodynamically stable and translucent dispersions of oil and water with a droplet size in the range 100-600 nm. Nanoemulsions are prepared by lowenergy methods such as phase inversion temperature (PIT) emulsification, by phase inversion composition or by high shear forces using high-pressure homogenizers or ultrasonic generators [5,6]. Mixed emulsions: these are systems consisting of two different disperse droplets that do not mix in a continuous medium Several breakdown processes may occur on storage depending on particle size distribution and density difference between the droplets and the medium [7,8].…”
Section: Introductionmentioning
confidence: 99%